(untitled) (Global Journal of Management and Business Research, 2019)
The aim of this study was to explore factors influencing decision quality made in public institutions in Jordan. On the basis of the literature, four factors were determined as factors associated to decision quality; moral intensity, information quality, group cohesiveness and decision experience. Each factor along with decision quality was assessed using six indicators adopted from previous studies. A questionnaire was developed and utilized in this study to collect data. The population of the study comprised managers, assistant managers and authorized employees to participate in decision making in 15 public institutions in Irbid governorate in Jordan. The total number of population was 210 participants, all of them included in the study. A total of 210questionnaires were distributed to the participants and 179 were returned complete with a response rate of 85.23%. Using SPSS and Amos to analyze the data, the results accepted the hypotheses that moral intensity, information quality, group cohesiveness and decision experience were significantly and positively have an influence on decision quality. It was found that group cohesiveness had the highest influence on decision quality, followed by information quality, then decision experience and finally moral intensity. The study concluded that decision quality is a function of three factors pertained to individuals and group features as well as quality of information required for the process. The main contribution of this study was represented by showing that individuals#x2019; knowledge and skills, participation in past decisions, and job description relevance are not enough unless they are supplemented by social consensus, certainty of decision effects, awareness of urgency of the situation, interpersonal attraction, commitment to task, and group pride, before having a locus of control on information dissemination and processing besides a perceived sufficiency of information.